2019
DOI: 10.26417/ejed-2019.v2i2-60
|View full text |Cite
|
Sign up to set email alerts
|

Low Cost Private Schools: ‘Helping’ to Reach Education for All Through Exploiting Women

Abstract: The rapid growth of Low Cost Private Schools (LCPS) in developing countries has led to increasing interest in the model’s ‘sustainability’. Nearly all the literature is based on the proponents’ claims that the model is more cost-effective than government schools rather than of the implications of the model depending to a large extent on very low paid young women teachers.The article is written against the backdrop of the model of an autonomous, respected, well-prepared teacher and framed in terms of human righ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The gendered inequities in the households of the teacher-participants, the institutional betrayal by the schools in the study, and the tactical strategies of resistance employed by the participants should not be viewed as developments peculiar to the pandemic. Even before COVID-19, Indian women were spending maximum hours globally on unpaid care work (OECD, 2018), private schools were being run with minimum checks and Saini balances (Ali, 2015;Carr-Hill & Sauerhaft, 2019), and women were practicing strategies of negotiation within the patriarchal settings of their families (Kohli, 2016). What the pandemic did was exacerbate and expose the fissures and inequities already present within the private school system and the heterosexual family system.…”
Section: Discussionmentioning
confidence: 99%
“…The gendered inequities in the households of the teacher-participants, the institutional betrayal by the schools in the study, and the tactical strategies of resistance employed by the participants should not be viewed as developments peculiar to the pandemic. Even before COVID-19, Indian women were spending maximum hours globally on unpaid care work (OECD, 2018), private schools were being run with minimum checks and Saini balances (Ali, 2015;Carr-Hill & Sauerhaft, 2019), and women were practicing strategies of negotiation within the patriarchal settings of their families (Kohli, 2016). What the pandemic did was exacerbate and expose the fissures and inequities already present within the private school system and the heterosexual family system.…”
Section: Discussionmentioning
confidence: 99%
“…However, during personal communications, teachers reported that their salaries were in the range of ₹1,800 to ₹5,000 8 per month. In other states of India too, LFP school teacher salaries are reported to be low (Carr-Hill & Sauerhaft, 2019;Kamat et. al., 2016;Sarangapani & Winch, 2010).…”
Section: Research Methodology and Settingmentioning
confidence: 99%
“…Kamat et al (2016) in her work with Hyderabad LFP schools reported average teachers’ salary to be $54 (₹4,138). Carr-hill reports similar teachers’ salaries in Gujrat Gyan Shala schools (Carr-Hill & Sauerhaft, 2019)…”
mentioning
confidence: 99%
“…They tend to find lower satisfaction in work because limited by the quality they have and the working conditions are not good (Chau, 2016;Kabeer, 2017;Pradhan et al, 2015). For example, in education, underpaid female teachers in private schools have denied human rights, and disempowered those marginalized and excluded (Carr-Hill & Sauerhaft, 2019).…”
Section: Not From a Rich And Educated Familymentioning
confidence: 99%